2008
DOI: 10.1111/j.1365-4632.2008.03804.x
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse cutaneous leishmaniasis associated with the immune reconstitution inflammatory syndrome

Abstract: Leishmaniasis is an emerging disease in HIV-infected persons; visceral leishmaniasis is an AIDS-defining opportunistic infection. The parasite that causes this infection is usually transmitted by the sandfly and occasionally by nonsterile needles among intravenous drug users. Diffuse cutaneous leishmaniasis (DCL) is a rare anergic variant of leishmanial infection with the characteristic presentation of numerous nonulcerating nodules with an abundant parasite load, lack of visceral involvement, negative reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 70 publications
0
30
0
1
Order By: Relevance
“…These patients tend to produce elevated levels of anti- Leishmania antibodies and excessive amounts of proinflammatory cytokines (e.g., IFN-γ, TNF-α, and IL-6) [15, 17]. Large-scale, gene polymorphism studies indicated that promoter polymorphisms for high production of IL-10 by monocytes and regulatory T (T reg ) cells increase the risk of CL lesions [18], whereas polymorphisms for high production of IL-6 and CCL2 increase the risk of ML, but not of localized CL [19, 20]. These studies may indicate a differential link between the host genetic predisposition for dysregulated inflammatory responses and the risk of severe infections.…”
Section: Non-healing Human Diseases Associated With L Braziliensis Imentioning
confidence: 99%
See 1 more Smart Citation
“…These patients tend to produce elevated levels of anti- Leishmania antibodies and excessive amounts of proinflammatory cytokines (e.g., IFN-γ, TNF-α, and IL-6) [15, 17]. Large-scale, gene polymorphism studies indicated that promoter polymorphisms for high production of IL-10 by monocytes and regulatory T (T reg ) cells increase the risk of CL lesions [18], whereas polymorphisms for high production of IL-6 and CCL2 increase the risk of ML, but not of localized CL [19, 20]. These studies may indicate a differential link between the host genetic predisposition for dysregulated inflammatory responses and the risk of severe infections.…”
Section: Non-healing Human Diseases Associated With L Braziliensis Imentioning
confidence: 99%
“…In patients with Leishmania tropica , L. major , or L. donovani infections in India and Africa, DCL or disseminated CL is also considered a clinical indicator of HIV co-infection [40, 41]. There is also a case report of DCL that developed in the context of the immune reconstitution inflammatory syndrome in a man with AIDS following initiation of antiretroviral therapy [18]. Generally speaking, patients with DCL share some clinical characteristics.…”
Section: Non-healing Human Diseases Associated With L Amazonensis Anmentioning
confidence: 99%
“…In the literature, few cases of leishmaniasis that developed in the context of IRS were described, and all occurred in patients co-infected with HIV. 5,[7][8][9] Here, we report, for the first time, that VL can also be an underlying disease predisposing to the development of IRS. We investigated the immunologic environment through dosages of serum biomarkers, including cytokines, soluble histocompatibility-leukocyte-antigen-G (sHLA-G) molecule and indoleamine 2,3-dioxygenase (IDO) activity.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with suppressed immune systems: ATL infection is emerging as a result of immunosuppression, and HIV is the most common cause 62,[75][76][77][78][79][80][81][82][83][84][85][86][87][88] . Bone marrow or solid organ transplantation [89][90][91][92][93][94][95] and therapy with immunosuppressive or biologic drugs [96][97][98] also have been associated with the appearance of ATL.…”
Section: Resultsmentioning
confidence: 99%
“…syndrome: the association between ATL and HIV-AIDS has increasingly been described in many regions of the world 99 together with immune reconstitution infl ammatory syndrome presentation 82,84,85,100 .…”
Section: Human Immunodefi Ciency Virus/acquired Immunodefi Ciencymentioning
confidence: 99%